DEPTH OF GENERAL ANESTHESIA: CLINICAL SIGNIFICANCE, MONITORING STRATEGIES, AND CURRENT CONTROVERSIES - Magdalena Rumin; Amanda Dolores Abramowicz; Kornelia Anna Domagała; Olga Tatarata; Maja Osuch; Maciej Osuch; Anna Kiełboń; Martyna Jaciubek; Carmena Luty; Zuzanna Olga Reklewska (International Journal of Innovative Technologies in Social Science, 2026)
Research Objectives: The depth of general anesthesia is a critical yet incompletely defined component of modern anesthetic practice. Both insufficient and excessively deep anesthesia have been associated with adverse intraoperative and postoperative outcomes, particularly in vulnerable patient populations. This narrative review aims to summarize current evidence on the clinical significance of anesthetic depth, discuss available monitoring strategies, and explore major limitations and controversies related to depth-of-anesthesia assessment, with particular emphasis on electroencephalography (EEG)-based monitoring.Methods: A narrative review of experimental, observational, and clinical studies was conducted using the PubMed/MEDLINE and PubMed Central databases. Publications published between 2005 and 2025 were included, supplemented by selected foundational studies addressing the neurophysiological mechanisms of consciousness and anesthesia. In total, 40 peer-reviewed publications were analyzed. The review focused on the dynamic nature of general anesthesia, the risks associated with excessive anesthetic depth, and the performance, benefits, and limitations of EEG-based monitoring techniques, including the bispectral index and entropy.Conclusions: General anesthesia represents a dynamic and multidimensional neurophysiological process rather than a binary loss of consciousness. Evidence suggests that excessively deep anesthesia is associated with cardiovascular depression, intraoperative hypotension, pathological EEG patterns, and an increased risk of postoperative delirium and cognitive dysfunction. EEG-based depth-of-anesthesia monitoring provides indirect insight into cerebral activity and may support anesthetic titration, reduction of excessive dosing, and improved hemodynamic stability. However, inter-device variability, susceptibility to artifacts, population-specific responses, and the absence of universally accepted cutoff values limit its use as a standalone tool. Depth-of-anesthesia monitoring should therefore complement comprehensive clinical assessment. Future research should focus on methodological standardization, multimodal monitoring, and individualized anesthetic strategies to improve perioperative safety.